2021
DOI: 10.18632/aging.203221
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol protects against early brain injury after subarachnoid hemorrhage in rats through alleviating blood-brain barrier disruption and blocking necroptosis

Abstract: Background: Subarachnoid hemorrhage (SAH) is a life-threatening disease worldwide, and effective pharmaceutical treatment is still lacking. Celastrol is a plant-derived triterpene which showed neuroprotective potential in several types of brain insults. This study aimed to investigate the effects of celastrol on early brain injury (EBI) after SAH. Methods: A total of sixty-one male Sprague-Dawley rats were used in this study. Rat SAH endovascular perforation model was established to mimic the pathological chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…These effects were related to celastrol induced activation of MAPKs and PI3K/Akt/mTOR pathways [ 30 ]. Celastrol ameliorated tight junction protein disruption after rat subarachnoid hemorrhage (SAH) to protect BBB integrity by decreasing MMP-9 expression and attenuating pro-inflammatory cytokines expression [ 31 ]. Celastrol is a BBB-penetrable compound, which may lay a foundation for maintaining the integrity of BBB and treating CNS disorders [ 32 ].…”
Section: Effects Of Celastrol On Cns Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects were related to celastrol induced activation of MAPKs and PI3K/Akt/mTOR pathways [ 30 ]. Celastrol ameliorated tight junction protein disruption after rat subarachnoid hemorrhage (SAH) to protect BBB integrity by decreasing MMP-9 expression and attenuating pro-inflammatory cytokines expression [ 31 ]. Celastrol is a BBB-penetrable compound, which may lay a foundation for maintaining the integrity of BBB and treating CNS disorders [ 32 ].…”
Section: Effects Of Celastrol On Cns Cellsmentioning
confidence: 99%
“…Celastrol significant attenuated I/R-induced hippocampal injury by inhibiting the AK005401/MAP3K12 signaling and activating the PI3K/Akt pathway [ 71 ]. In addition, celastrol attenuated brain swelling and protected the barrier function of BBB in the SAH rats [ 31 ]. Overall, celastrol shows obvious neuroprotective roles in a variety of stroke models, and how to promote its clinical transformation is the focus of next research.…”
Section: Neuroprotective Effects Of Celastrol In Neurodegenerative Di...mentioning
confidence: 99%
“… Chen et al (2019a) reported that anti-TNF-α treatment can significantly improve endothelial cell necroptosis and blood-brain barrier damage and further improve nerve function after stroke. In a SAH experimental study, celastrol administration decreased the expression levels of necroptosis-related proteins RIPK3 and MLKL, which exhibited neuroprotective effects on EBI ( Xu et al, 2021 ). Similarly, necrostatin-1, a small-molecule inhibitor of necroptosis, can potentially prevent SAH-induced necroptosis by suppressing the activity of the RIPK3/MLKL signaling pathway ( Chen et al, 2019b ).…”
Section: Neuronal Necroptosismentioning
confidence: 99%
“…Additionally, celastrol was shown to protect against early brain injury (EBI) after subarachnoid haemorrhage (SAH) [ 92 ]. In the rat SAH endovascular perforation model, celastrol improves neurological function, reduces brain swelling caused by SAH, and T2 lesion volume and ventricular volume.…”
Section: Celastrol Against Cerebrovascular Injurymentioning
confidence: 99%